Understanding antimicrobial use in subsistence farmers in Chikwawa District Malawi, implications for public awareness campaigns. - Eleanor E MacPherson; Joanna Reynolds; Esnart Sanudi; Alexander Nkaombe; John Mankhomwa; Justin Dixon; Clare I R Chandler (Public Library of Science (PLoS), 2022)
Drug resistant infections are increasing across the world and urgent action is required to preserve current classes of antibiotics. Antibiotic use practices in low-and-middle-income countries have gained international attention, especially as antibiotics are often accessed beyond the formal health system. Public awareness campaigns have gained popularity, often conceptualising antimicrobial resistance (AMR) as a problem of excess, precipitated by irrational behaviour. Insufficient attention has been paid to people's lived experiences of accessing medicines in low-income contexts. In Chikwawa District, Malawi, a place of extreme scarcity, our study aimed to understand the care and medicine use practices of households dependent on subsistence farming. Adopting an anthropological approach, we undertook medicine interviews (100), ethnographic fieldwork (six-month period) and key informant interviews (33) with a range of participants in two villages in rural Chikwawa. The most frequently used drugs were cotrimoxazole and amoxicillin, not considered to be of critical importance to human health. Participants recognised that keeping, sharing, and buying medicines informally was not the "right thing." However, they described using antibiotics and other medicines in these ways due to conditions of extreme precarity, the costs and limitations of seeking formal care in the public sector, and the inevitability of future illness. Our findings emphasise the need in contexts of extreme scarcity to equip policy actors with interventions to address AMR through strengthening health systems, rather than public awareness campaigns that foreground overuse and the dangers of using antibiotics beyond the formal sector.